Synthesis and characterization of Ni and Pd nanoparticles in natural rubber latex and their catalytic activity for hydrogenation of latex - Nurul Ain, Ramli (2013)
Natural rubber latex (NRL) is widely used as raw materials for rubber based products. The use of nLatex based polymer is constrained by its degradation in the environment due to the presence of carbon-carbon double bonds in their polymer backbone. Modifications of NRL via catalytic hydrogenation overcome this limitation. This research investigated the synthesis of Ni and Pd nanoparticles (NPs) in latex and determined the catalytic performances of both nanoparticles for the hydrogenation of latex. The effects of synthesis method, pH, sonication time and concentration of latex and metal ions precursor towards the formation of metal nanoparticles (Me-NPs) were studied. Transmission electron microscopy (TEM) was employed to study the morphology and particle size distribution of the NPs. The interactions between NPs with latex were studied using Fourier transform infrared (FTIR) spectroscopy. The catalytic hydrogenations of NRL by asprepared NPs were studied under different reaction conditions in order to investigate the effect of these variables towards the extent of hydrogenation. These include the effect of catalyst amount, nanoparticles size and solvent types. The structure, morphology and degree of hydrogenation of the hydrogenated NRL were determined by FTIR, scanning electron microscopy (SEM), field emission scanning electron microscopy (FESEM) and 1H nuclear magnetic resonance (NMR) spectroscopy respectively. Latex was found to be able to stabilize Ni and Pd NPs. Preparation involving the combination of ultrasonication and microwave irradiation upon the addition of NaBH4 into latex and metal ion mixture resulted in the most well dispersed NPs. The particle size of the NPs decreases as pH, sonication time, and stabilizer concentration increases. However, the particle size increases with the increase of metal ions precursor’s concentration. It was found that 10 ml of 0.003 M metal ions precursor concentration with 30 ml of stabilizer at pH 11.50 exposed to 15 minutes of sonication is an optimum condition to synthesize Ni-NRL and Pd-NRL. Under this preparation condition, the mean size of Ni-NRL was 10.8±0.3 nm while that for Pd-NRL was 30.6±2.9 nm. Hydrogenation of NRL using as-prepared NPs showed that the degree of hydrogenation increases with catalyst amount. The extent of hydrogenation is dependent on the particles sizes of the Ni-NRL but weakly dependent on and Pd-NRL NPs. Under similar reaction condition, Pd-NRL caused higher conversion than that of Ni-NRL. Monochlorobenzene was observed to be a suitable solvent for the hydrogenation reaction. Aqueous phase catalytic hydrogenations of NRL by the Ni-NRL and Pd-NRL were also investigated and found to cause 30% conversion compared to 70% for that in monochlorobenzene. Quadrupling the amount of nanocatalyst used to 2.4 x 10-5 mole led to 90% conversion of latex. Hence in this research it was found that not only the nanoparticles of Ni and Pd could be formed and stabilized in natural rubber latex but they could catalyze the hydrogenation reaction of the latex. It was also found that the nanoparticles could also facilitate the hydrogenation reaction in aqueous medium at moderate condition indicating the possibility of green catalysis for hydrogenation of latex.